A Novel Pan-Genome Reverse Vaccinology Approach Employing a Negative-Selection Strategy for Screening Surface-Exposed Antigens against leptospirosis - Zeng, LingBing; Wang, Dongliang; Hu, NiYa; Zhu, Qing; Chen, Kaishen; Dong, Ke; Zhang, Yan; Yao, YuFeng; Guo, XiaoKui; Chang, Yung-Fu; Zhu, YongZhang (Frontiers in Microbiology, 2017)
Reverse vaccinology (RV) has been widely used for screening of surface-exposed proteins (PSEs) of important pathogens, including outer membrane proteins (OMPs) and extracellular proteins (ECPs) as potential vaccine candidates. In this study, we applied a novel RV negative strategy and a pan-genome analysis for screening of PSEs from 17 L. interrogans strains covering 11 predominately epidemic serovars and 17 multilocus typing (MLST) sequence types (STs) worldwide. Our results showed, for instance, out of a total of 633 predicted PSEs in strain56601, 92.8% were OMPs or ECPs (588/633). Among the 17 strains, 190 core PSEs, 913 dispensable PSEs and 861 unique PSEs were identified. Of the 190 PSEs, 121 were further predicted to be highly antigenic and thus may serve as potential vaccine candidates against leptospirosis. With the exception of LipL45, OmpL1 and LigB, the majority of the 121 PSEs were newly identified antigens. For example, hypothetical proteins BatC, LipL71 and the OmpA family proteins sharing many common features, such as surface-exposed localization, universal conservation and eliciting strong antibody responses in patients, are regarded as the most promising vaccine antigens. Additionally, a wide array of potential virulence factors among the predicted PSEs including TonB-dependent receptor, sphingomyelinase 2, leucine-rich repeat protein and 4 neighboring hypothetical proteins were identified as potential antigenicity and deserve further investigation. Our results can contribute to the prediction of suitable antigens as potential vaccine candidates against leptospirosis and also provide further insights into mechanisms of leptospiral pathogenicity. In addition, our novel negative-screening strategy combined with pan-genome analysis can be a routine RV method applied to numerous other pathogens.